Cytologic features of gastric‐type adenocarcinoma of the uterine cervix. Issue 10 (14th July 2015) - Kawakami, Fumi; Mikami, Yoshiki; Sudo, Tamotsu; Fujiwara, Kiyoshi; Hirose, Takanori; Itoh, Tomoo
<x xml:space="preserve">Abstract</x> Background Gastric‐type mucinous carcinoma (GAS) is a clinically aggressive variant of cervical adenocarcinoma. This study sought to describe the cytologic features of GAS. Methods We reviewed the cervical and endometrial smears of 14 patients with a histopathologic diagnosis of GAS. All slides were conventionally smeared. We included 20 controls with usual‐type endocervical adenocarcinoma (UEA). Results Monolayered and honeycomb sheets were observed in 78.6% (11/14) of patients with GAS, and were prominent in seven patients. Three‐dimensional clusters were more prominent in the UEA group. Vacuolar and/or foamy cytoplasm was observed in 71.4% (10/14) of patients with GAS, whereas this finding was rare among those with UEA (2/18). Marked intracytoplasmic neutrophil entrapment was more common in the GAS group (7/14) than in the UEA group (2/18). Intracytoplasmic mucin was present in eight patients with GAS. Nuclei were vesicular in eight patients with GAS, but were homogenous and hyperchromatic in UEA patients. Conspicuous nucleoli were present in nine patients with GAS. Conversely, this finding was rarely observed in UEA patients. Conclusions The characteristic cytologic findings of GAS include (1) monolayered and honeycomb sheets, (2) vacuolar and/or foamy cytoplasm, (3) intracytoplasmic neutrophil entrapment, and (4) vesicular nuclei with prominent nucleoli. Diagn. Cytopathol. 2015;43:791–796. © 2015 Wiley Periodicals, Inc.